Pengaruh Gaya Mengajar Guru Dan Minat Belajar Terhadap Prestasi Belajar Siswa Kelas VIII DI SMP Negeri 12 Pematang Siantar Tahun ajaran 2022/2023 - Dio Chandra Parhusip; Anggun Tiur Ida Sinaga; Tumpal Manahara Siahaan (CV. KAMPUS AKADEMIK PUBLISING, 2023)
This study aims to obtain knowledge about the influence of teacher teaching styles and learning interests on the learning achievement of grade VIII students at SMP Negeri 12 Pematang Siantar for the 2023/2024 academic year. This type of research is quantitative with an ex-post facto approach with the testing media used is SPSS 22. The total population in this study was 286 people, and the sample used was 170 people. The sample collection technique used is the Proportionate Stratified Random Sampling Technique. The data collection technique used is a questionnaire (questionnaire). The hypothesis data collection technique uses multiple regression analysis and coefficient of determination (R2).The results stated that: 1) There is a positive and significant influence of teacher teaching style on learning achievement, this result is seen in the t test where the t value iscalculated from learning interest (5,710) > the t value of thetable (1.6540) which means that the variable is significant. (2) There is a positive and significant influence of learning interest on student achievement, this result is seen in the t test where and thecalculated t value of peers (3.020) > ttable (1.6540) which means that the variable is significant. 3) The teacher's teaching style and interest in learning together affect student achievement ( this result can be seen in the F test wherethe calculated F value (34.117) >the table F value (3.0501). The R Square coefficient of determination test is known to be 0.291, which means 29.1% of the variables of teacher teaching style and learning interest in learning achievement of grade VIII students of SMP Negeri 12 Pematang Siantar. While 70.9% is the influence of other variables that were not studied in this study.,